Kreativität zwischen Schöpfung und Zerstörung: Konzepte aus Kulturwissenschaften, Psychologie, Neurobiologie und ihre praktischen Anwendungen - Holm-Hadulla, Rainer M. (Vandenhoeck & Ruprecht, 2011)
The idea of creativity enjoys great popularity: Everywhere inventiveness is perceived as something of high value. Whether in education, training, professional activities or everyday life, creative processes are considered important and valuable. Yet there is a considerable ambiguity as to what creativity actually means. Neurobiologists, for example, think creativity is determined by the speed and complexity of one’s information processing. Psychologists, on the other hand, point to the “flow” accompanying all creative activities and the parallel release of endorphines. Cultural scientists concern themselves with the “kiss of the muse” and describe complex processes of creation. Throughout there is a lack of a coherent theory describing creative processes which could serve to further creativity in both the educational milieu and in professional and personal life.This volume by Rainer M. Holm-Hadulla provides a synthesis of cultural, psychological and neurobiological perceptions of creativity. He emphasizes the interplay between creation and destruction, order and chaos, construction and deconstruction. This results in many practical consequences for both ordinary and extraordinary forms of creativity. Artistic personalities such as Goethe and Jim Morrison provide examples of how humans display and use their ambivalent creative powers.
Keywords: Kreativität; Psychologie; Kulturwissenschaften